1993
DOI: 10.1111/j.2044-8325.1993.tb00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the relationship of locus of control to different performance dimensions

Abstract: Using a sample of 146 bank tellers, this study tested the usefulness of locus of control for explaining initiative versus compliant performance. Based upon Spector's (1982) conceptual work, locus of control showed a negative relationship to initiative performance and a positive relationship to compliant performance. However, these results were only found using Spector's (1988) work locus of control measure and not with the Rotter (1966) meas'ure. Spector's work locus of control measure also explained Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
63
0
20

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 59 publications
3
63
0
20
Order By: Relevance
“…This claim is supported by studies, which have indicated that WLCS is a better predictor of work behavior than the generalized measure of locus of control (Blau, 1993;Orpen, 1992). WLCS has been used in several studies concerning e.g.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…This claim is supported by studies, which have indicated that WLCS is a better predictor of work behavior than the generalized measure of locus of control (Blau, 1993;Orpen, 1992). WLCS has been used in several studies concerning e.g.…”
Section: Introductionsupporting
confidence: 67%
“…Furthermore, stressors seem to have less effect on well-being for individuals who have internal locus of control (Daniels & Guppy, 1994;Lu et al, 2000). Several studies have also revealed that internal WLC is positively related to different organizational outcomes such as motivation, job performance, job satisfaction, perception of organizational climate and organizational commitment (Blau, 1993;Furnham & Drakeley, 1993;Lu et al, 2000;Orpen, 1992;Ross, 1991). The results of Cvetanovski and Jex's study (1994) showed that unemployed people with internal locus of control were more satisfied with life and also felt better both psycho-logically and physically than externals.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations